Optimization of the Lifetime and Cost of a PMSM in an Electric Vehicle Drive Train - Aissam Riad Meddour; Nassim Rizoug; Patrick Leserf; Christopher Vagg; Richard Burke; Cherif Larouci (Energies, 2023)
This study focuses on optimizing the lifetime and cost of an electric vehicle powertrain by optimizing the motor’s geometrical parameters and the bus voltage while considering the battery’s sizing. We employ the WLTP driving cycle to evaluate the powertrain’s performance and use finite element and analytical modeling to consider electromagnetic, thermal, and aging behaviors. Our research investigates the interplay between the battery and motor, exploring how varying the motor geometry and parameters affects the powertrain’s overall lifetime and cost. Our findings will contribute to developing more efficient and cost-effective electric powertrains.